A medida de confiar é confiar sem medida? Estudo sobre o efeito da confiança na criação e na captura de valor na relação comprador-fornecedor - Martins, Guilherme Silveira (2013)
This study aims to analyze the effect of trust on both value creation and value capture in the buyer-supplier relationships. We have started from Relational Vision perspective, in which collaborative relationships are able to create a single value that would not be created by any of partnership members independently, even in a simple market exchange. Trust plays a central role in collaborative relationships, since it acts as an effective relational governance mechanism. Therefore, it minimizes transaction costs, such as those related to monitoring and controlling, and it promotes firms engagement in value creation activities. However, whereas value creation is a winwin scenario, in value capture, it means that, if a bigger slice of pie is taken by a firm, a smaller slice is left to the other firm. Thus, despite the importance of presence of trust to promote collaborative relationships, its excess makes firm forbear from bargain power use, meaning it would hand out to a partner a share of the gains that would be appropriated by the firm. The study was conducted on 117 dyads of Brazilian chemical industry, based on this industry firm’s relationships with buyers from others industries. Structural equation modeling and multiple regression techniques have formed the multivariate data analysis. Our results demonstrated the existence of both 'bright side' and 'dark side' of trust. Although the importance of trust was evident in relational rents creation on dyads, we found a limit to the benefits of the growing level of confidence. In excess, it actually hurts the potential of suppliers in capturing value. Our results also indicate that suppliers’ potential in capturing relational rents was hampered by high dependence in a particular buyer. Theoretical and managerial implications are discussed.